Disengaging from engagement: Exploring the potential drivers of Performance management - Fukey, Leena Nitin; Vaithilingam, Bharathi Muthu (International Journal of Psychosocial Rehabilitation, 2020)
Employee Engagement emerged as a significant important topicin organizations over the recent years.This concept gained even more importance since many drivers have been identified to influence Employee Engagement. Since Human Resources were considered to be the most valuable resource in any organization, well- being of employees was one of the aspects that HR managers focus on. It could be found in literature that organizations that could engage their employees better,achieved greater efficiency in their operations. The term ‘Employee Engagement’ was first coined by Professor Kahn in 1990 (Khan, 1990). Since then, it has become one of the main interests of many academicians and practitioners. Several studies have been conducted to study how to improve Employee Engagement within organizations.The objective of this paper was to identify the key drivers of Employee Engagement impacting Employee performance from previous studies, through literature review, and to assesshow these drivers induce the performance of employees in Management Consulting Firms.Review of past literature on the topic was done through electronic databases.Moreover, this paper also reviewed the four most impactful factors that affected Employee Engagement, in depth, while also providing links to opinions from people in a variety of workspaces, via the help of surveys and questionnaires.